An urban epidemic — an audit of an inner city young persons' clinic. (1st January 2002) - Burns, F; Curran, B; Tobin, R; Kell, P
In 1996 a young persons' clinic was set up at the Archway Sexual Health Clinic. A retrospective case note review of all attendees for 7 months in 1999 was performed to assess the demography and incidence of sexually transmitted infections (STIs) amongst attenders of the clinic. There were 567 attendances, comprising 364 individuals (331 women and 33 men). Ten per cent of attendees were less than 16 years of age, and 48% were 16-18 years. Fifty-eight per cent were from ethnic minorities. Chlamydial and gonococcal infection was identified in 21.3% and 8.4%, respectively. Thirty-five per cent of new presentations by women involved pregnancy testing, 28.6% were positive. The introduction of the clinic has been successful judged both by the amount of attendances and diseases diagnosed. Specific provision of services for this group needs to be addressed by all sexual health providers.